Semantica lessicale dei verbi sintagmatici in italiano. Analisi intra-/interlinguistica del VS mettere fuori - Marcol, Lucyna (Neophilologica, 2010)
The aim of this paper is to describe the phenomenon of syntagmatic verbs in Italian language with a following analysis of one of them mettere fuori. Every derived meaning of mettere fuori is followed by an example of the phrase in which it can be used together with its translation into Polish. The scrutiny is aimed at proving that mettere fuori is not infrequently accompanied with an auxiliary object before the exact one. The author of the article emphasizes the problem both of the particularity of syntagmatic verbs in Italian and of the research of their equivalents in Polish.